University of Florida Potato Variety Trial Spotlight: ‘Goldrush’ - Rodrick Z. Mwatuwa; Christian T. Christensen; Pam Solano; Lincoln Zotarelli (EDIS)
by Rodrick Z. Mwatuwa, Christian T. Christensen, Pam Solano, and Lincoln Zotarelli http://edis.ifas.ufl.edu/hs1299